Health economics and quality of life in a feasibility RCT of paediatric acute appendicitis: a protocol study. Issue 1 (21st September 2018) - Chorozoglou, Maria; Reading, Isabel; Eaton, Simon; Hutchings, Natalie; Hall, Nigel J
Abstract : Background: Acute appendicitis is one of the most common acute surgical emergencies in children and accounts for an annual cost of approximately £50 million to the National Health Service. Investigating alternative treatment options offers the best prospect of enhancing the quality of care for patients and potential opportunities for cost savings through better allocative efficiency. A feasibility randomised controlled trial (RCT) comparing a non-operative treatment pathway with appendicectomy for children with acute uncomplicated appendicitis is underway (CONTRACT feasibility RCT). Aims: The prime objective of this economic substudy conducted alongside the CONTRACT feasibility RCT is to better understand and assess: (1) cost data collection tools and cost drivers by identifying patients' pathways and (2) patient quality of life by assessing alternative paediatric health-related quality of life (HRQoL) instruments. Outcomes from this study will inform a future efficacy RCT assessing the effectiveness and cost-effectiveness of non-operative treatment pathway for the treatment of acute uncomplicated appendicitis in children. Methods: The economic substudy will use individual-level data and will be conducted from the health system perspective over the study's 6-month follow-up period. Microcosting will include health resource and service use, while potential benefits acquired will be measured using the HRQoL measures, Child Health Utility 9D (CHU-9D) and Euroqol-5 dimensions and 5 levels (EQ-5D-5L). We will assess the appropriateness of using the cost per quality-adjusted life year framework in the future RCT, as well as testing and identifying the most suitable HRQoL instrument. Conclusions: The outcomes of the investigational economic substudy will be used to inform the design of our future definitive RCT. However, the result from this economic study will also provide a detailed description and account of the issues inherent in paediatric Economic Evaluations Alongside Clinical Trials with an emphasis on costing methods of interventions taking place in secondary care settings. Trial registration number: ISRCTN1583043 .